Photoelastic Analysis of Stress Distribution in Different Retention Systems for Facial Prosthesis - Goiato, Marcelo Coelho [UNESP]; Ribeiro, Paula do Prado [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Garcia Júnior, Idelmo Rangel [UNESP]; Pesqueira, Aldieris Alves [UNESP]; Haddad, Marcela Filie [UNESP] (Lippincott Williams & Wilkins, 2009)
The aim of this study was to assess the behavior and stress distribution of 3 retention systems associated with implant for facial prosthesis by using the photoelasticity method. A photoelastic model was made from the replica of the orbital region on the left side of a dry skull with two 4-mm implants fixed in the superior orbital region. Three facial prosthetic retention systems were made for this study: O'ring, bar-clip, and magnets. The set (model/retention systems/prosthesis) was placed in a polariscope, and then traction began to be applied to the retention systems. The limit values for removal of the retention system were obtained by tests performed in an EMIC Universal test machine. The results were obtained by observation during the experiments and by photographic record of the stress behavior in the photoelastic model, resulting from the traction of the retention systems. In the magnet system, a lowest formation of fringes was verified both around and between the implants; in the O'ring system, the formation of photoelastic fringes was noted between the implants in the apical region; and in the bar-clip system, there was a greater concentration of colored fringes in the regions between the implants and cervical area. Based on the results obtained, it was concluded that the retention systems produced different stress distribution characteristics that, in general, were concentrated in the area around the implants, and the highest concentration of fringes, in increasing order, occurred ill the retention systems of the magnets, O'ring, and bar-clip.
Keywords: Dental implants; maxillofacial prosthesis; photoelasticity